Supporting competence in practitioners working in personality disorder services. Issue 4 (14th November 2016) - Johnson, Helen; Gredecki, Neil; Wilks-Riley, Fiona Rachel
Abstract : Purpose: The purpose of this paper is to provide a "spotlight" on the literature relating the selection, recruitment and development of staff working in personality disorder (PD) services. Design/methodology/approach: The paper reviews key documentation in the field of PD practice in relation to staff. Findings: Despite the publication of guidelines for working with PD clients, a number of large scale enquiries suggest that some services have often failed to absorb and implement the recommendations made which has resulted in serious consequences. Practical implications: A number of considerations relating to enhancing staff competency when working in PD units are presented. Originality/value: The review outlines a number of good practice guidelines relating to the different stages of recruitment and employment for staff working with PD clients.